Fungsi Kesenian Rebana sebagai Media Pengembangan Masyarakat Islami (Studi Kasus Pengusaha Rebana Muslim Grup Kecamatan Manyar Gresik) - Fuji Fitria Ningsih (Jurnal Al-Tatwir, 2021)
Village is one of culture drivers as well as a pioneer in maintaining and preserving the culture in a region. However, technological advances and globalization as it is today are able to accelerate the rate of transformation of a region's arts, especially music. Therefore, it is necessary to have various strategies to educate the society, especially the younger generation, to better understand, appreciate and preserve various traditional musical arts as part of the existing cultural diversity. The current research is a descriptive qualitative research which primary and secondary data were obtained from observation or documentation. The subject of the current study is 'Bumi Sholawat' or 'Banjari' of Muslim Rebana entrepreneur group in Manyar, Gresik. The influence of Rebana art on Islamic society with the existence of a Rebana production house from the Muslim Group is that there are many Islamic activities and associations to learn together from and to spread the love of sholawat in Manyar, Gresik. In addition to that, the youth can get benefits from the sale of Rebana. They also hold a prayer routine using Rebana on Friday nights. Many events are held in Manyar subdistrict and several institutions come to collaborate on major Islamic events. Lastly, besides strengthening the friendship between fellow Muslims, people need art for the necessities of life, while art requires people as its supporters. As supporters, it is hoped that people can preserve and develop art through new works that are adaptive to the current situation and conditions. Whether we realize it or not, developing an art form cannot be separated, and it always intersects with other aspects, such as social, economic, beliefs, customs, and so on.